Prevalence and Host Resistance to Common Bean Rust Disease in Western and Central Kenya - Brian W. Wafula; Edith E. Arunga; Felix Rotich (International Journal of Agronomy)
Rust, caused by Uromyces appendiculatus (Pers.) Unger, is among the most devastating diseases of the common bean (Phaseolus vulgaris L.) worldwide. The pathogen is highly genetically variable, causing severe epidemics under favourable weather conditions. The objectives of this study were to determine the distribution of bean rust in major production areas in Kenya and identify potential sources of resistance for breeding. A field survey was conducted in five counties targeting smallholder common bean farmers in western and central Kenya, where data on the incidence and severity of bean rust and crop management practices by farmers were recorded. Additionally, seeds of the evaluated genotypes were collected from farms visited for further testing. A total of 77 common bean genotypes were subjected to natural infection under field conditions and inoculated with races 29–1, 29–3, 61–1, and 63–1 of rust under greenhouse conditions at the University of Embu. The gene pool affiliation of the genotypes was determined through the phaseolin protein marker analysis. Rust incidence and severity data were subjected to an analysis of variance using GenStat statistical software. The results showed that bean rust occurred in all counties although there were significant differences (P<0.001) in incidence and severity among the surveyed localities. Based on a 1–9 severity rating scale, Bungoma County recorded the highest mean severity of 3.99 and an incidence of 71%. Cultivar grown, use of fungicides, management of residues, and crop spacing had a significant effect on bean rust severity. Under field and greenhouse conditions, the genotypes revealed high variations in response to rust, with 71% of the genotypes being susceptible under greenhouse inoculations. Enclave, MU#13, UN2-Darkgreen, UN6-Nakholo, Kat X56, and KMR-11 genotypes were identified as resistant and can be used as prospective parents in common bean improvement programs in Kenya. This study revealed high occurrence and distribution of common bean rust and thus provides critical baseline information for common bean rust management in Kenya.